High‐resolution melting curve FRET‐PCR rapidly identifies SARS‐CoV‐2 mutations. Issue 9 (22nd June 2021) - Barua, Subarna; Hoque, Monirul; Kelly, Patrick J.; Bai, Jianfa; Hanzlicek, Gregg; Noll, Lance; Walz, Heather; Johnson, Calvin; Kyriakis, Constantinos; Wang, Chengming
Abstract: Reverse transcription fluorescence resonance energy transfer‐polymerase chain reaction (FRET‐PCRs) were designed against the two most common mutations in severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) (A23403G in the spike protein; C14408T in the RNA‐dependent RNA polymerase). Based on high‐resolution melting curve analysis, the reverse transcription (RT) FRET‐PCRs identified the mutations in american type culture collection control viruses, and feline and human clinical samples. All major makes of PCR machines can perform melting curve analysis and thus further specifically designed FRET‐PCRs could enable active surveillance for mutations and variants in countries where genome sequencing is not readily available. Highlights: A23403G in the spike protein and C14408T in the RNA‐dependent RNA polymerase are identified as two most common mutations in the SARS‐CoV‐2 variants. Reverse transcription FRET‐PCRs identified the mutations while no DNA sequencing required. Designed FRET‐PCRs could enable active surveillance for mutations and variants in countries where genome sequencing is not readily available.